2017
DOI: 10.1371/journal.pone.0174779
|View full text |Cite
|
Sign up to set email alerts
|

Vector-free intracellular delivery by reversible permeabilization

Abstract: Despite advances in intracellular delivery technologies, efficient methods are still required that are vector-free, can address a wide range of cargo types and can be applied to cells that are difficult to transfect whilst maintaining cell viability. We have developed a novel vector-free method that uses reversible permeabilization to achieve rapid intracellular delivery of cargos with varying composition, properties and size. A permeabilizing delivery solution was developed that contains a low level of ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…As an example, significant membrane defects have been reported in membranes exposed to only 1% butanol 1329 . One case where ethanol is used for intracellular delivery purposes was report by O’Dea et al Ethanol sprayed with an atomizer was used to reversibility permeabilize cells for intracellular delivery of proteins, mRNA, and plasmids 1330 .…”
Section: Intracellular Delivery By Permeabilizationmentioning
confidence: 99%
“…As an example, significant membrane defects have been reported in membranes exposed to only 1% butanol 1329 . One case where ethanol is used for intracellular delivery purposes was report by O’Dea et al Ethanol sprayed with an atomizer was used to reversibility permeabilize cells for intracellular delivery of proteins, mRNA, and plasmids 1330 .…”
Section: Intracellular Delivery By Permeabilizationmentioning
confidence: 99%
“…used ethanol as a permeabilizing agent for intracellular delivery purposes and demonstrated that the 25% v/v concentration of this alcohol provides the optimal permeabilization condition. [ 20 ] Studies have shown that ethanol remains at the water–lipid interface to induce disordering effect on phospholipid acyl chains leading to partially destroy the plasma membrane bilayer structure. [ 20,89 ]…”
Section: Macroengineered Intracellular Deliverymentioning
confidence: 99%
“…[ 19 ] Once chemical modifications, extensive mechanical forces, or high‐intensity energies are introduced to the cells, the plasma membrane will experience the perturbation state, which triggers an increase in membrane deformation and permeability of the exogenous cargo. [ 20 ] Upon intracellular cargo delivery, the cell would reseal the disruptions through the active membrane and cytoplasmic recovery processes, which largely depend on the cell type, pore size, temperature and the factors presented in the extracellular medium. [ 21 ] Studies have proposed up to six different plasma membrane resealing mechanisms (e.g., exocytosis) that are implicated in active membrane repair.…”
Section: Introductionmentioning
confidence: 99%
“…4d), effectively controlling loading. Avectas has a delivery efficiency of ~53% and a cell survival of 78% (for comparison, the efficiency and cell survival are 93% and 73%, respectively for electroporation) 94 . For most methods, effective delivery must be balanced with maintenance of cell viability to provide a scalable solution (Avectas is also developing a closed continuous system for GMP manufacturing).…”
Section: Production Of Car-t Cells and Haematopoietic Stem Cellsmentioning
confidence: 99%